Synthesis and characterization of polymeric composite adsorbents for the removal of radioactive materials from wastewater / Michael Adekunle Olatunji - Michael, Adekunle Olatunji (2017)
The research focused on the synthesis of polypyrrole conducting polymer derivatives for the removal of 109Cd, 137Cs and 60Co radionuclides. The polypyrrole-based adsorbents (pure polpyrrole, surfactant-doped polypyrrole, polypyrrole/sawdust composite and polypyrrole/activated carbon composite) were characterized by FESEM, HR-TEM, BET, FTIR, XRD, TG-DTG and Boehm titration methods. All the polypyrrole materials were successfully tested to remove 109Cd, 137Cs and 60Co radionuclides from aqueous solutions. The preliminary investigations revealed that the composite materials have higher removal percentage for the radionuclides than the pure polypyrrole. Comparison of the removal by the composites revealed that the polypyrrole/ activated carbon composite prepared in the presence of anionic surfactant had higher removal percentage for all the radionuclides than the polypyrrole/sawdust composite prepared with or without the anionic surfactant. Consequently, the effect of the experimental variables on adsorption of the radioactive materials were investigated by using composites of surfactant-doped polypyrrole (PPy/SDBS) and surfactant-doped polypyrrole/activated carbon (PPy/SDBS/AC) and the results were compared with that of pure polypyrrole (PPy). For all polypyrrole adsorbents, the effect shows increasing the uptake of the radionuclides with increasing solution pH, initial ion concentration, contact time and temperature, except for 109Cd radionuclide that decreased with increasing the temperature. In all cases, equilibrium adsorption was achieved within 240 min contact time and at a pH of 6. The maximum adsorption capacities were realized with PPy/SDBS/AC composite in order of 35.3 mgCd.g‒1, 23.0 mgCs.g‒1 and 18.1 mgCo.g‒1, followed by PPy/SDBS adsorbent in the order of 16.0 mgCd.g‒1, 14.2 mgCs.g‒1 and 13.5 mgCo.g‒1 and PPy adsorbent in the order of 9.78 mgCo.g‒1, 8.96 mgCd.g‒1 and 6.40 mgCs.g‒1, respectively. In the bi-solute adsorption system, the maximum adsorption capacities for the competitive adsorption are ranked as 137Cs > 109Cd > 60Co. The effect of random irradiation of the as-prepared polypyrrole adsorbents with 100 and 200 kGy gamma doses on the adsorption capacity showed to be practically negligible, except for the surfactant-doped polypyrrole/activated carbon composite which showed relatively higher sorption capacity. The desorption of the spent polypyrrole-based adsorbents was successful with 0.1 ‒ 1 M HCl, but adsorption by the recycled adsorbents was not successful after 4 cycles.